Conceptual foundations of entrustable professional activities for health professional education in Latin America - López, María José (2022)
The concept of entrustable professional activities emerged as an attempt to overcome some of the criticisms to the competency-based medical education approach; it has had a broad impact in practice and health professions education research. It has been disseminated internationally with its English acronym: EPA. This approach proposes to orient assessment and teaching to specific activities in the profession, which allows the integration of several competencies, and to determine which responsibilities can be entrusted to the trainee, in a gradual and explicit manner. The model assumes the definition of levels of supervision that allow progressive autonomy for each EPA, in students or residents, once they demonstrate the required competencies. Practice, supervision and feedback in real clinical scenarios are key to the development of autonomy in EPA performance. The dissemination of the EPA approach is still limited in Latin America, but it has the potential to create a significant contribution to curriculum design and evaluation, and to assessment practices of health professionals across their careers. It provides a deep review of the assumptions under which healthcare professional practice decisions are made, at under and postgraduate levels.